Peran Dewan Pengawas Syariah (DPS) Dan Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) Dalam Pengembangan Industri Wisata Halal Indonesia - Noor Kholifah Hidayati; Ro'fah Setyowati; Ninik Zakiyah (Universitas Muhammadiyah Surabaya, 2021)
AbstractThe synergy of DPS and DSN-MUI as a determinant of the implementation of Islamic principles in the financial sector greatly influences the development of sharia economic law in Indonesia. Sharia Economic Law such as the fatwa product from the DSN-MUI should be able to become a legal umbrella for the financial sector and the real sharia sector in Indonesia, but in fact the influence given by the fatwa and its regulators, namely the DSN-MUI and DPS in the real and financial sectors is still deemed not balanced. This paper uses a normative-juridical method with a historical approach, a conceptual approach and a law approach, and uses a qualitative juridical analysis method. The results show that, first, the role of DSN-MUI as an external supervisor and DPS as an internal supervisor has a major influence on sharia compliance in the financial sector. Second, the dominance of the touch of DSN-MUI and DPS only exists in the Islamic finance sector, while the real sector has not been closely monitored by DPS. Third, the real sector of the halal tourism industry that is labeled with sharia still does not meet the sharia compliance principles specified in the DSN-MUI fatwa. This study is important considering the fact that the role of the DSN-MUI in issuing fatwas on new sharia products and supervision of DPS in the real sector must be carried out immediately because the real sector in the sharia industry has developed a lot and can reduce the level of trust of the sharia economy community if it is not accompanied by proper guidelines and supervision. optimal.Keywords: DSN-MUI; DPS; halal tourism; financial sector; real sectorAbstrakSinergitas DPS dan DSN-MUI sebagai penentu implementasi prinsip Islam pada sektor keuangan sangat mempengaruhi perkembangan hukum ekonomi syariah di Indonesia. Hukum Ekonomi Syariah seperti produk fatwa dari DSN-MUI mestinya dapat menjadi payung hukum bagi sektor keuangan dan sektor riil syariah di Indonesia, namun faktanya pengaruh yang diberikan dari fatwa tersebut beserta regulatornya yaitu DSN-MUI dan DPS pada sektor riil dan keuangan masih dirasa belum seimbang. Tulisan ini menggunakan metode yuridis-normatif dengan pendekatan historis, pendekatan konseptual dan pendekatan Undang-Undang, serta menggunakan metode analisis yuridis kualitatif. Hasil penelitian menunjukkan bahwa, pertama, peran DSN-MUI sebagai pengawas eksternal dan DPS sebagai pengawas internal berpengaruh besar pada kepatuhan prinsip syariah di sektor keuangan. Kedua, dominasi sentuhan DSN-MUI dan DPS hanya ada di sektor keuangan syariah, sedangkan sektor riil belum diawasi secara ketat oleh DPS. Ketiga, sektor rill industri wisata halal yang berlabel syariah masih kurang memenuhi prinsip kepatuhan syariah yang ditentukan dalam fatwa DSN-MUI. Kajian ini menjadi penting melihat fakta bahwa peran DSN-MUI untuk mengeluarkan fatwa produk syariah baru dan pengawasan DPS pada sektor riil harus segera dilakukan karena sektor riil di indusri syariah telah banyak berkembang dan dapat menurunkan tingkat kepercayaan masyarakat ekonomi syariah jika tidak diiringi pedoman dan pengawasan yang optimal.Kata kunci: DSN-MUI; DPS; wisata halal; sektor keuangan; sektor riil